An investigation into the mediators of talent in field hockey: factors that affect successful talent identification and development - Turnbull, J. (2011)
This investigation was conducted to gain an understanding of the career pathways of current international female field hockey performers, and their experiences of talent identification and development. There is limited specific research within field hockey and so often development programmes have been based upon findings in other sports. 12 female senior international field hockey players were interviewed for the investigation.\ud \ud The major influences on achieving elite performance in field hockey were identified as support from families, schools and clubs, with an overriding influence from luck at all stages. It is suggested that the type of school attended by the individual will have an impact upon the direction that their career will take.\ud \ud Literature suggested that school, club (Bailey and Morely 2006,) and family support (Kay, 2000) was a vital factor in achieving elite performance as well as luck (Bailey, 2006). Overall it was found that the influence of school is dominant for private school pupils (Priv-kids), whereas clubs are more important for grammar school (Gram-kids) and state school pupils (Stat-kids). Family and talent development programmes were found to be vitally important for all types of youth performers and so emphasises the need to make these as affective as possible and also to make them as accessible as possible for the talented youth performers, rather than just the lucky ones